Caffeine degradation by food microorganisms - TJAHJADI PURWOKO; SURANTO SURANTO; RATNA SETYANINGSIH; SOERYA DEWI MARLIYANA (Society for Indonesian Biodiversity, 2023)
Abstract. Purwoko T, Suranto, Setyaningsih R, Marliyana SD. 2023. Caffeine degradation by food microorganisms. Biodiversitas 24: 3495-3502. Commercial coffee beans are dominated by robusta and arabica coffee beans. Caffeine is one of the important components in coffee beans. Caffeine has antimicrobial effect. Caffeine content in robusta beans was higher than in arabica beans. Caffeine content in coffee beans was affected by the coffee species, the coffee cultivation's altitude and the postharvest processing method. Microbial fermentation activity could reduce the caffeine content of coffee beans. Lactobacillus casei, Leuconostoc mesenteroides, Rhizopus oryzae and Saccharomyces cerevisiae, were able to reduce caffeine content of robusta beans. This study aimed to determine the degradation pathway of caffeine by food microorganisms, namely L. casei, L. mesenteroides, R. oryzae and S. cerevisiae. Caffeine content in NB-caffeine and PDB-caffeine media were reduced by L. casei, L. mesenteroides, R. oryzae and S. cerevisiae. Caffeine was transformed into dimethylxanthine and then into methylxanthine by L. casei, L. mesenteroides, R. oryzae and S. cerevisiae. They transformed more than 89% caffeine into paraxanthine, however, small amount of paraxanthine was transformed into methylxanthine. L. casei and L. mesenteroides transformed paraxanthine into 1-methylxanthine. However, R. oryzae and S. cerevisiae transformed into 7-methylxanthine. There were two patterns of degradation of caffeine into methylxanthine i.e., caffeine-paraxanthine-1-methylxanthine and caffeine-paraxanthine-7-methylxanthine. The first was shown by L. casei and L. mesenteroides, and the last by R. oryzae and S. cerevisiae.